PENGARUH GYPSUM DAN PUPUK FOSFAT TERHADAP PENYERAPAN LOGAM CROMIUM DAN NIKEL SERTA PERTUMBUHAN TANAMAN JARAK (Jatropha curcas L.) DI TANAH SERPENTIN - Yuliani Ekawati; Badruzsaufari Badruzsaufari; Akhmad R. Saidy (Bioscientiae, 2009)
This research aim to know giving influence of gypsum and phosphate fertilisers to absorbtion of nickel heavy metal and chromium and plant growth of distance planted at serpentine soil;land;ground. Serpentine soil;land;ground media is given gypsum and phosphate fertilisers with a few kinds of composition for gypsum 110 g and phosphate fertilisers 0,875 g, fence castor is planted during 8 week and height is measured each week. Chromium rate and nickel in crop is measured and considers wet weight and crop drought. Growth parameter observed is cotyledon height, plant height and number of leaves. Result of research indicates that giving of gypsum and phosphate at serpentine soil;land;ground cannot lessen absorption of nickel by castor network that is 69,25 ppm for gypsum, giving of phosphate 71,75 ppm, giving gypsum + phosphate 67,75 ppm and (control) 81,75 ppm. However, can lessen absorption of chromium by castor network that is is not is given treatment amelioran (control) be 45,50 ppm. Giving gypsum, phosphate and gypsum + phosphate unable to detect chromium content in crop. Giving of gypsum and phosphate doesn't give real influence to growth parameter observed.